Bone marrow mesenchymal stem cells reduce ureteral stricture formation in a rat model via the paracrine effect of extracellular vesicles. Issue 9 (11th July 2018) - Luo, Jintai; Zhao, Shankun; Wang, Jiamin; Luo, Lianmin; Li, Ermao; Zhu, Zhiguo; Liu, Yangzhou; Kang, Ran; Zhao, Zhigang
Abstract: With no effective therapy to prevent or treat ureteral stricture (US), a multifactorial fibrotic disease after iatrogenic injury of the ureter, the need for new therapies is urgent. Mesenchymal stem cells (MSCs) have been widely studied for treating tissue defects and excessive fibrosis, and recent studies established that one of the main therapeutic vectors of MSCs is comprised in their secretome and represented by extracellular vesicles (EVs). Thus, we have determined to explore the specific role of MSCs‐derived EVs (MSC‐EVs) treatment in a pre‐clinical model of US. The results firstly showed that either a bolus dose of MSCs or a bolus dose of MSC‐EVs (administration via renal‐arterial) significantly ameliorated ureteral fibrosis and recuperated ureter morphological development in a US rat model. We confirmed our observations through MSCs or MSC‐EVs treatment alleviated hydronephrosis, less renal dysfunction and blunted transforming growth factor‐β1 induced fibration. Due to MSC‐EVs are the equivalent dose of MSCs, and similar curative effects of transplantation of MSCs and MSC‐EVs were observed, we speculated the curative effect of MSCs in treating US might on account of the release of EVs through paracrine mechanisms. Our study demonstrated an innovative strategy to counteract ureteral stricture formation in a rat model of US.